2006
DOI: 10.1007/s00586-006-0143-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between sitting and occupational LBP

Abstract: Low back pain (LBP) has been identified as one of the most costly disorders among the worldwide working population. Sitting has been associated with risk of developing LBP. The purpose of this literature review is to assemble and describe evidence of research on the association between sitting and the presence of LBP. The systematic literature review was restricted to those occupations that require sitting for more than half of working time and where workers have physical co-exposure factors such as whole body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
299
0
30

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 455 publications
(342 citation statements)
references
References 65 publications
13
299
0
30
Order By: Relevance
“…New kinematic parameters could be presented to rate dynamic and isometric trunk and spine action. It can be expected that further occupational analyses will provide new insights into these highly relevant data of spine loads at the workplace [30]. Furthermore, these data could be of paramount importance for prevention and rehabilitation and to appreciate ergonomic measures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…New kinematic parameters could be presented to rate dynamic and isometric trunk and spine action. It can be expected that further occupational analyses will provide new insights into these highly relevant data of spine loads at the workplace [30]. Furthermore, these data could be of paramount importance for prevention and rehabilitation and to appreciate ergonomic measures.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned in the introduction, only weightbearing tasks can be drawn upon to document occupationspecific strain on the lower back. In industrial workplaces, however, the overwhelming majority of employees are not primarily affected by load bearing tasks [30]. Monotonous, unilateral tasks with static or repetitive demands are common in industrial jobs [5,23].…”
Section: Discussionmentioning
confidence: 99%
“…OR and RR in the studies that indicated statistical significance showed the range of 1.2 to 39.5 and 1.7, respectively (Bernard et al, 1997). Lis et al reported that occupational groups exposed to WBV while sitting are at an increased risk of having LBP (OR is over 1.7), and the influence of the duration of the exposure seems more important than the magnitude of the exposure in cumulative effect, though sitting by itself did not increase the association with the present LBP (Lis et al, 2007).…”
Section: Physical Factorsmentioning
confidence: 85%
“…Low back pain and neck pain are major health problems in the computer workplace 1,13) . Maintaining a slumped sitting posture is a risk factor for work-related muscular disorders and is closely associated with the incidence of low back pain 11,14,15) .…”
Section: Discussionmentioning
confidence: 99%